Exercise tolerance and balance of inspiratory-to-expiratory muscle strength in relation to breathing timing in patients with chronic obstructive pulmonary disease. (28th March 2018) - Miki, Keisuke; Tsujino, Kazuyuki; Edahiro, Ryuya; Kitada, Seigo; Miki, Mari; Yoshimura, Kenji; Kagawa, Hiroyuki; Oshitani, Yohei; Ohara, Yuko; Hosono, Yuki; Kurebe, Hiroyuki; Maekura, Ryoji
Abstract: Rationale . Little is known about the applicability of respiratory muscle training based on exertional pathophysiological conditions in patients with chronic obstructive pulmonary disease (COPD). The aim of this study was to investigate the relationship between breathing timing and exertional responses, as well as whether exertional changes in the inspiratory duty cycle (Ti/Ttot) affect pathophysiological conditions, including respiratory muscles. Methods . Forty-five stable COPD patients (mean age: 71.2 years, severe and very severe COPD: 80%) were evaluated based on exertional cardiopulmonary function and respiratory muscle strength. To compare exertional responses and the balance of inspiratory-to-expiratory muscle strength, the patients were divided into two groups according to whether the Ti/Ttot increased (Ti/Ttot-increased group: resting Ti/Ttot ≤ peak Ti/Ttot, n = 21) or decreased during exercise (Ti/Ttot-decreased group: resting Ti/Ttot > peak Ti/Ttot, n = 24). Results . At peak exercise, the Ti/Ttot was positively correlated with minute ventilation ( V ̇ E ), and oxygen uptake ( V ̇ O 2 ) in all patients. No significant differences were seen in breathing frequency, tidal volume, or V ̇ E at peak exercise between the two groups. Compared with the Ti/Ttot-increased group, the Ti/Ttot-decreased group had significantly lower mean values of V ̇ O 2 and ΔFO2 (the inspired minus expired oxygen concentration) at peak exercise, and significantly higher mean values of the absolute ratio of maximal inspiratory pressure/maximal expiratory pressure. Conclusions . The exertional change of breathing timing affected exercise tolerance and the balance of inspiratory-to-expiratory muscle strength; this finding might be helpful in making the contradictory choice of managing COPD patients with inspiratory or expiratory muscle training.